Digital Marketing sebagai Optimalisasi Strategi Pemasaran Wirausaha Muda “Clothing PRJBus dalam Meningkatkan Omset Bisnis UMKM - Putri, Synthia Sumartini (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Digital marketing is now the key to online-based marketing to promote its products. Economic sector and Micro, Small and Medium Enterprises. Business Entities (MSMEs) have felt the impact since the current pandemic. Especially young entrepreneurs who are in the bus clothing business. The clothing bus business was initially established since covid hit in 2021. The purpose of this study is to find out how these young entrepreneurs optimize digital marketing to increase their MSME turnover. This study uses a phenomenological method which is a type of qualitative research to interpret and explain someone's experience or experience. Data collection techniques using interviews, observation and documentation. The results of the data that the researchers found that the clothing bus business was carried out by a young person, digital marketing using advertising, marketing, and social media content so that it could invite the public from various regions. Marketing that is used through celebrity endorsements in order to attract public attention.